2019
DOI: 10.5194/acp-19-747-2019
|View full text |Cite
|
Sign up to set email alerts
|

A new interpretative framework for below-cloud effects on stable water isotopes in vapour and rain

Abstract: Abstract. Raindrops interact with water vapour in ambient air while sedimenting from the cloud base to the ground. They constantly exchange water molecules with the environment and, in sub-saturated air, they evaporate partially or entirely. The latter of these below-cloud processes is important for predicting the resulting surface rainfall amount. It also influences the boundary layer profiles of temperature and moisture through evaporative latent cooling and humidity changes. However, despite its importance,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 47 publications
4
79
1
Order By: Relevance
“…These variations integrate all processes along air mass trajectories (Figure 4, blue dashed square). The third term (Figure 4, magenta dashed square) represents a combination of precipitation‐vapor disequilibrium effects (due to variations in condensation altitude or postcondensation processes such as rain evaporation), variations in the vertical gradients between the surface (where the precipitation achieves its last equilibration, e.g., Graf et al, 2019) and 5 km (where the water vapor δ 2 H is observed by IASI) and small‐scale variations in water vapor δ 2 H (leading to difference between the water vapor δ 2 H observed by IASI and that with which the precipitation locally equilibrates).…”
Section: Methodsmentioning
confidence: 99%
“…These variations integrate all processes along air mass trajectories (Figure 4, blue dashed square). The third term (Figure 4, magenta dashed square) represents a combination of precipitation‐vapor disequilibrium effects (due to variations in condensation altitude or postcondensation processes such as rain evaporation), variations in the vertical gradients between the surface (where the precipitation achieves its last equilibration, e.g., Graf et al, 2019) and 5 km (where the water vapor δ 2 H is observed by IASI) and small‐scale variations in water vapor δ 2 H (leading to difference between the water vapor δ 2 H observed by IASI and that with which the precipitation locally equilibrates).…”
Section: Methodsmentioning
confidence: 99%
“…The Craig and Gordon (1965) model has been applied and refined in various studies and has been shown to adequately simulate the isotopic composition of the MBL water vapour under evaporative conditions (e.g. Merlivat and Jouzel, 1979;Gat, 2008;Horita et al, 2008;Pfahl and Wernli, 2009;Benetti et al, 2018;Feng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This effect can be quantified in a model, but it is very difficult to quantify in nature because it is complicated and uncertain to measure η (Rosenfeld and Mintz, 1988), and it is even more complicated to measure or predict α evap . Rain evaporation can have a depleting or enriching effect depending on microphysical details that are too complex to be addressed here (Graf et al, 2019). Neglecting rain evaporation leads to an error of the order of 500 m in regions of low EIS and 250 m in regions of strong EIS (Fig.…”
Section: Neglecting Rain Evaporationmentioning
confidence: 99%